Updated recommendations on the management of gastrointestinal disturbances during iron chelation therapy with Deferasirox in transfusion dependent patients with myelodysplastic syndrome: emphasis on optimized dosing schedules and new formulations - Nolte, Florian; Hofmann, Wolf-Karsten (Leukemia research, 2015)
Myelodysplastic syndromes (MDS) are oligoclonal hematopoietic disorders characterized by peripheral cytopenias with anemias being the most prevalent feature. The majority of patients will depend on regular transfusions of packed red blood cells (PRBC) during the course of the disease. Particularly patients with MDS and low risk for transformation into acute myeloid leukemia and low risk of early death will receive PRBC transfusions on a regular basis, which puts them at high risk for transfusional iron overload. Transfusion dependence has been associated with negative impact on organ function and reduced life expectancy. Recently, several retrospective but also some prospective studies have indicated, that transfusion dependent patients with MDS might benefit from consequent iron chelation with regard to morbidity and mortality. However, low treatment adherence due to adverse events mainly gastrointestinal in nature is an important obstacle in achieving sufficient iron chelation in MDS patients. Here, we will summarize and discuss the existing data on Deferasirox in low risk MDS published so far and provide recommendations for optimal management of gastrointestinal adverse events during iron chelation aiming at improving treatment compliance and, hence, sufficiently removing excess iron from the patients.
Gesehen am 20.03.2018